Organoenergetic Investigation on the Potential of Industrial Brewers' Spent Grain Valorization for Biogas Production - Zacharie Merlin Ayissi; Bernard Nchare; Nazia Hossain; Severin Mbog; Stéphane Lontsi Kenfack; Dieudonné Bitondo (Advanced Energy Conversion Materials, 2024)
Cameroon is a high country producer and consumer of beer in Africa which has various breweries generating a large amount of brewer spent grain (BSG) yearly. This study was designed to investigate the potential use of spent grains derived from the Cameroonian brewing industry as a viable and sustainable energy source for biogas production. A comprehensive proximate analysis was performed, focusing on key physicochemical parameters including moisture content, acidity level, ash content, and the proportions of proteins, carbohydrates, and fats, thereby enabling the derivation of their energy value to determine the organoenergetic profile. Physicochemical characterization of the spent grains revealed a pH of 5.6, moisture content of 8%, and ash content of 9.8% at 450 °C for 2 h using a muffle furnace. The organic composition included a high iron content of 194.2 mg/100 g, an organic matter content of 99%, a total organic carbon (TOC) content of 57.39%, a total nitrogen content of 3%, and a nitrogen-carbon ratio of 19.13%. In addition, the spent grains exhibited substantial concentrations of total protein (18.75%), crude fiber (3.6%), lipids (8.7%), and carbohydrates (51.15%), with an energy value of 14.97 MJ/kg. Moreover, the chemical oxygen demand (COD) was determined to be 3,880 mg/kg, while the lower calorific value (LCV) was 19.76 MJ/kg, resulting in a COD/TOC ratio of 86.03. These findings showed that the spent grain from Cameroonian brewery has a significant organ energetic potential based on its components and physicochemical properties, thereby highlighting their suitability as a valuable resource for biogas generation.